Rancang Bangun Platform Intel Edison Sebagai IoT Gateway Berbasis Protokol MQTT - Anggit Wicaksana; Bakhtiar Alldino Ardi Sumbodo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
The role of IoT gateway on IoT network is vital, like for strengthen the sensor management. Accordingly, in this research designed an IoT gateway based on MQTT Protocol which implemented in Intel Edison platform and using ten node sensors with star topology.Results from this research is an IoT gateway system who capable to receive data packet from node sensor, saves the data in database, and publishes the data to MQTT broker. User able to do data acquisition by subscribe method, using MQTT Dasboard application. The system tested by doing the calculation of time response of gateway with variation of data length and variation of distance, life time of node sensor testing by the variation of data length. The conclusions are the time average of from data acquisition by node sensor until gateway saves the data in database and user subscribes the data is twelve seconds. The shorter the data length makes the response time of gateway faster and makes the life time of node sensor shorter because the measured current is bigger. The distance is not gives any impact to the response time of gateway.